2018
DOI: 10.3390/microorganisms6020034
|View full text |Cite
|
Sign up to set email alerts
|

Non-Psychrophilic Methanogens Capable of Growth Following Long-Term Extreme Temperature Changes, with Application to Mars

Abstract: Although the martian environment is currently cold and dry, geomorphological features on the surface of the planet indicate relatively recent (<4 My) freeze/thaw episodes. Additionally, the recent detections of near-subsurface ice as well as hydrated salts within recurring slope lineae suggest potentially habitable micro-environments within the martian subsurface. On Earth, microbial communities are often active at sub-freezing temperatures within permafrost, especially within the active layer, which experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…This is predominately due to the difficultly in simulating the relatively high pressures associated with these environments. For example, when investigating the effect of Mars conditions on microbial growth, experiments are routinely conducted in glass containers (e.g., Schirmack et al 2015;Mickol et al 2018), which are unable to sustain pressures above 1 bar. To alleviate this issue, high pressure reactors are used.…”
Section: High Pressure Simulation Facilitiesmentioning
confidence: 99%
“…This is predominately due to the difficultly in simulating the relatively high pressures associated with these environments. For example, when investigating the effect of Mars conditions on microbial growth, experiments are routinely conducted in glass containers (e.g., Schirmack et al 2015;Mickol et al 2018), which are unable to sustain pressures above 1 bar. To alleviate this issue, high pressure reactors are used.…”
Section: High Pressure Simulation Facilitiesmentioning
confidence: 99%
“…Nevertheless, the development of new effective techniques for the detection of putative life beyond Earth is still an important problem to be solved (Nadeau et al, 2008;Garcia-Descalzo et al, 2012;Judge, 2017;Nelis et al, 2018). The basic astrobiological methods are mostly related to search for biosignatures of a geological, chemical, and biomorphological nature (Cockell, 2010;Westall et al, 2015;Hays et al, 2017;Mickol et al, 2018). Here, we propose a novel nanobiotechnological approach for the detection of microbiological objects in water or melted ice samples from extraterrestrial low-temperature environments.…”
Section: Introductionmentioning
confidence: 99%
“…Ulrich et al (2012) discussed the potential habitability of periglacial landscapes in martian midlatitudes by relating terrestrial analogs to permafrost landforms on Mars. Subsurface permafrost environments on Mars represent potential habitable regions where extant life could have survived (Cockell, 2014;Schirmack et al, 2014); additionally, terrestrial permafrost is considered the most promising analog to a potential martian habitat Mickol et al, 2018). Microbial communities in terrestrial permafrost and coldassociated environments often appear in high density and consist of specialized cold-adapted microorganisms (Wagner, 2008;Bajerski and Wagner, 2013;Mitzscherling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Methanogenic archaea from Siberian permafrost meet many of the preconditions for survival in the martian subsurface, showing a remarkable resistance against desiccation, osmotic stress, low temperatures, starvation, radiation, and thermophysical martian conditions as compared to non-permafrost strains Morozova et al, , 2015Morozova et al, 2015;Mickol et al, 2017). They are also a subject of astrobiological interest for future planetary exploration missions that involve life detection (de Vera et al, 2012;Serrano et al, 2014Serrano et al, , 2015Mickol et al, 2018;Taubner et al, 2018). Schuerger et al (2012) discussed the biotoxicity of multiple martian soils and concluded that they are not likely to be overtly toxic to terrestrial microorganisms.…”
Section: Introductionmentioning
confidence: 99%